Analisis Risiko Fraud Pada Penyaluran Kredit Usaha Rakyat (KUR) (Studi Kasus Pada Bank XYZ) - Susilo Kristiono S; Poerwaningsih S; Lis Sintha (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
During the last 3 (three) years, the quality of People's Business Credit (KUR) distribution at Bank XYZ showed an increase in the percentage of Non-Performing Loans (problematic loans), in addition to the number of claims rejected by the guarantee company has increased. The rejection of KUR claims is more dominantly due to the KUR distribution process not being in accordance with applicable provisions, including indications of fraud committed by bank employees. The impact of the KUR rejection caused bad debts to not be resolved, resulting in losses for the company. The results of risk measurement using the fishbond diagram obtained 11 causes of debtor defaults that were indicated as fraud grouped into 4 (four) aspects; process, people, policy, and system. Of the 11 causes of debtor defaults, there are 2 (two) causes classified as Supplementary Issues, which are recommended to take risk mitigation measures. By knowing the impact and opportunities for the occurrence of causes of debtor defaults, mitigation of possibilities and mitigation of impacts can be carried out appropriately and correctly, so that it is expected to reduce or even avoid the risks that will occur.